The Turkish Pension System Further Reforms to Help Solve the Informality Problem - Brook, Anne-Marie (OECD Social, Employment and Migration Working Papers, 2006)
Recent social security reform has significantly improved the long-run sustainability of the pension system. However, the pension system continues to serve as an important barrier to a more rapid expansion of the formal-sector economy in two ways. First, early-retirement incentives (including severance payments) continue to push many incumbent formal sector workers into the informal sector, often at ages as young as 40-45. While new labour force entrants face a much higher retirement age, policies for incumbents are fiscally expensive, inequitable, and serve to swell the ranks of the informal sector. Second, even when the transition to the new pension rules is complete, net replacement rates will remain very high by OECD standards, requiring high social security contribution rates that make it too expensive for firms to employ low-skilled labour in the formal sector. Thus, further pension reform is one of the keys to overcoming Turkey's economic duality. Finally, since the pension system does not cover the informal sector, it does little to alleviate poverty among the wider population of older people. This paper discusses a number of reforms that would increase the retirement age, reduce inter-generational inequities, and permit a significant cut in the tax wedge on labour, while better addressing old-age poverty concerns at all levels of income